Tribological mechanism of (Cr, V)N coating in the temperature range of 500–900 °C. (July 2021) - Wang, Cuicui; Xu, Beibei; Wang, Zhenyu; Li, Hao; Wang, Li; Chen, Rende; Wang, Aiying; Ke, Peiling
Abstract: Aiming to study the influence of temperature on the wear mechanism, we fabricated (Cr, V)N coating by cathodic arc ion-plated and conducted tribological experiments at 500–900 °C. The results indicated that there were two tribological behaviors, depending on the temperature. Below 600 °C, the (Cr, V)N coatings exhibited a high friction coefficient, but generated a mild wear because of the slight oxidation. Above 700 °C, the increased oxidation degree reduced adhesion of asperity contacts. However, the wear rate enhanced significantly with the temperature increasing from 700 to 900 °C due to the fast oxidation accompanied by the decrease in both hardness and adhesion strength. Highlights: Cr0.58 V0.14 N0.28 coating was successfully fabricated by cathodic arc technique. The relationship between oxidation, mechanics and friction was analyzed. The wear mechanism from 500 °C to 900 °C was divided into two stages. The best tribological properties of the coating were obtained at 700–800 °C.